القلق اللغوي في مهارة الكلام لدى طلاب المدرسة الابتدائية الإسلامية الحكومية مالانج - Azizah, Azizah (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2024)
ABSTRACT Anxiety is a factor that results in an individual's inability to carry on conversations smoothly and naturally, they are also sometimes unable to remember what they have prepared. Anxiety that is often researched tends to use student objects that are carried out in universities. Even though in fact anxiety is also often experienced by students at the Elementary level. Broadly speaking, this study aims to find out how description of language anxiety when practicing kalam learning on students at MIN 2 Malang City. The research method used is a qualitative approach with a descriptive research type. The research was conducted at MIN 2 Malang City in the 2022-2023 academic year, with a population of 10 grade IV students and 87 grade V students. From a number of existing population, a sample of 97 students was taken. The results showed that According to the results of in-class observations, the researcher can conclude that the description of anxiety in students at MIN 2 Malang City about learning kalam is the number of missing mufrodat and the use of tarkib which is not correct. Therefore, it can be concluded that students at MIN 2 Malang City show more responses on the physical aspect and most students are included in the medium indicator at the level of language anxiety when practicing kalam learning at MIN 2 Malang City. ملخص القلق اللغوي هو أحد العوامل التي تؤدي إلى عدم قدرة الفرد على الاستمرار في المحادثة بسلاسة وبشكل طبيعي، كما أنه في بعض الأحيان غير قادر على تذكر ما أعده. يميل القلق الذي يتم البحث عنه غالبًا إلى استخدام كائنات الطلاب التي يتم إجراؤها في الجامعة. على الرغم من أن القلق غالبًا ما يعاني منه الطلاب في المرحلة الابتدائية. بشكل عام، تهدف هذا البحث يعني كيف صورة القلق اللغوي عند عملية الكلام لدى طلاب في المدرسة الابتدائية الإسلامية الحكومية الثانية مالانج. منهج البحث المستخدم هو منهج نوعي بنوع بحث وصفي. تم إجراء البحث في مدرسة الإبتدائية الإسلامية الحكومية الثانية مالانج في العام الدراسي 2022-2023، ويبلغ عدد 10 طلاب بالصف الرابع و 87 طالبًا بالصف الخامس. من عدد من السكان الحاليين، تم أخذ عينة من 97 طالبًا. أظهرت نتائج البحث ما يلي عند نتائج الملاحظة في الفصل، تمكن للباحثة أن تستنتج أن وصف القلق لدى طلاب في المدرسة الابتدائية الإسلامية الحكومية الثانية مالانج حول تعليم الكلام هو عدد المفردات المفقودة واستخدام التراكيب الذي لا يتوافق. لذلك، يمكن استنتاج أن الطلاب في المدرسة الابتدائية الإسلامية الحكومية الثانية مالانج يظهرون ردودًا أكثر على الجانب الجسدي ويتم تضمين معظم الطلاب في المؤشر المعتدل ​​على مستوى القلق اللغوي عند ممارسة تعليم الكلام لدى طلاب في المدرسة الابتدائية الإسلامية الحكومية الثانية مالانج